2022
DOI: 10.2174/1566523221666210519111933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rat Bone Marrow Derived-Mesenchymal Stem Cells on Granulocyte Differentiation of Mononuclear Cells as Preclinical Agent in Cellbased Therapy

Abstract: Background: Bone marrow mononuclear cells (BM-MNCs), as a collection of hematopoietic and mesenchymal stem cells (MSCs), are capable of producing all blood cell lineages. The use of cytokines, growth factors, or cells capable of secreting these factors will help in stimulating the proliferation and differentiation of these cells into mature cell lines. On the other hand, MSCs are multipotent stromal cells that can be differentiated into various cell lineages. Moreover, these cells can control the process of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In a study by Fathi et al. (2021), it was reported that co-culturing of MNCs with rat BM-derived MSCs cause an increase in the expression levels of granulocyte markers of MNCs, e.g., CD34, CD16, CD11b, and CD18 [ 23 ]. Based on these data, one can conclude that MSCs may affect the granulocyte differentiation of MNCs via ERK protein expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Fathi et al. (2021), it was reported that co-culturing of MNCs with rat BM-derived MSCs cause an increase in the expression levels of granulocyte markers of MNCs, e.g., CD34, CD16, CD11b, and CD18 [ 23 ]. Based on these data, one can conclude that MSCs may affect the granulocyte differentiation of MNCs via ERK protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…BM mononuclear cells (MNCs) were collected using density gradient centrifugation as previously described by Fathi et al. (2022) [ 23 ]. For this purpose, the ethical code was obtained from the Committee on the Ethics of Tabriz University of Medical Sciences (EthicsNo.…”
Section: Methodsmentioning
confidence: 99%
“…Stained samples were measured in a BD Verse flow cytometer (BD Biosciences). FlowJo software version 10.2 (LLC, Ashland, OR, USA) was used to analyze the data [ 26 28 ].…”
Section: Methodsmentioning
confidence: 99%